EGFR-mediated Macrophage Activation Promotes Colitis-associated Tumorigenesis - Hardbower, Dana M. (Oncogene, 2017)
Epidermal growth factor receptor (EGFR) signaling is a known mediator of colorectal carcinogenesis. Studies have focused on the role of EGFR signaling in epithelial cells, although the exact nature of the role of EGFR in colorectal carcinogenesis remains a topic of debate. Here, we present evidence that EGFR signaling in myeloid cells, specifically macrophages, is critical for colon tumorigenesis in the AOM-DSS model of colitis-associated carcinogenesis (CAC). In a human tissue microarray, colonic macrophages demonstrated robust EGFR activation in the pre-cancerous stages of colitis and dysplasia. Utilizing the AOM-DSS model, mice with a myeloid-specific deletion of Egfr had significantly decreased tumor multiplicity and burden, protection from high-grade dysplasia, and significantly reduced colitis. Intriguingly, mice with gastrointestinal epithelial cell-specific Egfr deletion demonstrated no differences in tumorigenesis in the AOM-DSS model. The alterations in tumorigenesis in myeloid-specific Egfr knockout mice were accompanied by decreased macrophage, neutrophil, and T cell infiltration. Pro-tumorigenic M2 macrophage activation was diminished in myeloid-specific Egfr-deficient mice, as marked by decreased Arg1 and Il10 mRNA expression and decreased IL-4, IL-10 and IL-13 protein levels. Surprisingly, diminished M1 macrophage activation was also detectable, as marked by significantly reduced Nos2 and Il1b mRNA levels and decreased IFN-γ, TNF-α, and IL-1β protein levels. The alterations in M1 and M2 macrophage activation were confirmed in bone marrow-derived macrophages from mice with the myeloid-specific Egfr knockout. The combined effect of restrained M1 and M2 macrophage activation resulted in decreased production of pro-angiogenic factors, CXCL1 and VEGF, and reduced CD31(+) blood vessels, which likely contributed to protection from tumorigenesis. These data reveal that EGFR signaling in macrophages, but not in colonic epithelial cells, has a significant role in CAC. EGFR signaling in macrophages may prove to be an effective biomarker of CAC or target for chemoprevention in patients with inflammatory bowel disease.